The First Pregnancies in Turkey Following in Vitro Ooctye Maturation - Demirkol, Aygül; Sarı, Tamer; Girgin, Bağdagül; Kent, Erkin; Güven, Süleyman; Gurgan, Timur (Gynecology Obstetrics & Reproductive Medicine, 2006)
OBJECTIVE: To report pregnancies that resulted from the intracytoplasmic sperm injection (ICSI) of in vitro matured oocytes derived from two unstimulated, anovulatory patients with polycystic ovary syndrome. STUDY DESIGN: Two women with history of infertility and PCOS underwent in vitro maturation (IVM) program without controlled ovarian hyperstimulation. The patients were primed with 10.000 IU HCG 36 h before oocyte retrieval. Oocytes-cumulus masses were matured in IVM medium. The matured oocytes were fertilized by ICSI and embryo transfer was performed on day 3. RESULTS: For the first patient thirty-four GV-stage oocytes were collected, twenty two of them reached MII stage following 24-48 hour in vitro maturation, 17 of mature oocytes were fertilized by ICSI and the embryos were cultured for 3 days. Four embryos were transferred on day 3. In the second patient, 7 of 9 GV-stage oocyte retrieved were matured in vitro, 4 of them were fertilized by ICSI and 4 embryos were transferred on day 3. Both of the patients achieved clinical pregnancy. The first pregnancy resulted in abortion in 6th gestational weeks while the other one is still ongoing singleton pregnancy (nine weeks of gestation) CONCLUSIONS: Immature oocyte collection combined with IVM is a convenient option for infertile couple with PCOS compared to conventional assisted reproductive therapy.